Colin A. Roman, The Shorter Science and Civilisation in China; An Abridgment of Joseph Needham's Original Text. Volume 2: Volume III and a Section of Volume IV, Part 1, of The Major Series, Cambridge, Cambridge University Press, 1981, pp. xii + 459. - Maeth Ch., Russell (Estudios de Asia y África, 1983)
-